RESPON PEDAGANG BARANG HARIAN TRADISIONAL TERHADAP ALFAMART DAN INDOMART DI KECAMATAN TAMPAN PEKANBARU (JL. HR. SOEBRANTAS) - Yulida Hikmah Harahap; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted at HR. Soebrantas street Tampan district, Pekanbaru with the title Traders Resale Response Against Alfamart and Indomart in Tampan District, Pekanbaru (HR Soebrantas street). Lately, with the increasing technological advances population growth encouraged the increased development activities. One of the many developments done is the development in the field of shopping centers such as retail stores like Alfamart and Indomart. In the last 5 years, it has been known that retail store development has been done as many as 11 Alfamart and 12 Indomart on HR. Soebrantas street, Pekanbaru. Meanwhile, traditional traders sell similar products are found in the same location and have operated both before and after the establishment of the retail store. This study aims to find out how the traditional daily merchant’s response to the existence of Alfamart and Indomart on HR. Soebrantas street as well as to determine the extent to which the influence caused by Alfamart and Indomart to the turnover of traditional daily merchant on HR. Soebrantas street. The theory used in this research are the response and development theory, while the method used is quantitative descriptive by using questionnaires and guided interview techniques. The results showed that from 75 respondents there were 30 respondents who accepted, 29 respondents refused, and 16 respondents that did not care regarding the existence of Alfamart and Indomart. Based on this research, it can be concluded that the existence of Alfamart and Indomart didn’t affect the turnover of Traders Traditional Goods.  Keywords : Respond, effect, turnover